2018
DOI: 10.1038/s41598-018-32398-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Significant Carotid Stenosis for Nasopharyngeal Carcinoma between Intensity-Modulated Radiotherapy and Conventional Two-Dimensional Radiotherapy

Abstract: Radiotherapy (RT) serves as the most efficient treatment for nasopharyngeal carcinoma (NPC) and can cause carotid stenosis. This work compared the incidence of significant carotid stenosis between intensity-modulated radiotherapy (IMRT) and two-dimensional conventional radiotherapy (2D-RT) for NPC and explored the risk factors. We retrospectively reviewed 233 cases with NPC who underwent carotid ultrasound post IMRT or 2D-RT from 2006 to 2015. The incidence of significant stenosis after RT was 19.3%. Significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Despite this promising possibility of exposing NOS to higher doses, maintaining the exposure of the vast majority of nerves and chiasm segments to lower doses may be safe. In this context, it is noteworthy that, unlike conventional radiotherapy, in which a high dose is delivered to NOS targets by bilateral opposed fields, IMRT can deliver a higher radiation dose to the target region while sparing the adjacent optic nerves/chiasm by using multiple fields ( 32 ). Thus, only portions of the nerves, rather than the entire nerve, were subjected to the prescription dose at the targeted nerve level.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this promising possibility of exposing NOS to higher doses, maintaining the exposure of the vast majority of nerves and chiasm segments to lower doses may be safe. In this context, it is noteworthy that, unlike conventional radiotherapy, in which a high dose is delivered to NOS targets by bilateral opposed fields, IMRT can deliver a higher radiation dose to the target region while sparing the adjacent optic nerves/chiasm by using multiple fields ( 32 ). Thus, only portions of the nerves, rather than the entire nerve, were subjected to the prescription dose at the targeted nerve level.…”
Section: Discussionmentioning
confidence: 99%
“…Post-irradiation changes in the vessels develop over time. There are divergent opinions regarding the length of this period [18], [22], [23], [24], [25], [26], [27]. Cheng et al demonstrated an 8.5 times greater risk of having severe carotid stenosis in patients irradiated over 5 years ago than in those with a shorter history [24].…”
Section: Discussionmentioning
confidence: 99%
“…But there was no dose-response curve between the carotid absorbed dose and arterial stiffness for the head and neck patients after radiotherapy for 8 years [27]. Another study showed a significant increase in carotid artery stenosis after radiotherapy, but IMRT is lower than 2D radiotherapy [28]. Previous studies were focused on the Young elastic modulus after radiotherapy, but shear elastic modulus has not been investigated in radiation-induced vessels.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%